Optimization of Region of Interest (ROI) Image of Malaria Parasites - Rika Rosnelly; Linda Wahyuni; Jani Kusanti (Universitas Dian Nuswantoro and IndoCEISS, 2018)
The stage of region of interest (ROI) is the determining part to the next stage in image processing. ROI is a process of taking certain parts or regions in an image. ROI can be done by manual and automatic cropping. Some previous studies still use cropping manually for detection of malaria parasites. This study uses cropping automatically for detection of malaria parasites. The types of malaria parasites used were falciparum, vivax and malariae with ring stages, tropozoite, schizon and gametocytes. Data from malaria parasites were obtained at the North Sumatra Provincial Health Laboratory. The results show that the ROI image can crop the malaria parasite region.Â Keyword - malaria parasite, ROI.